2018
DOI: 10.1111/jomf.12459
|View full text |Cite
|
Sign up to set email alerts
|

Assortative Mating and the Intergenerational Transmission of Parental Incarceration Risks

Abstract: Research on the intergenerational transmission of incarceration tends to focus on patrilineality,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
1
8
0
1
Order By: Relevance
“…Step 3: Heterogeneity and robustness checks Given the markedly higher crime rates among men compared to women, the intergenerational transmission of crime often is seen as primarily operating between fathers and sons (Andersen, 2018), and we therefore present our findings by child's gender. Results for boys and girls separately (see Figure A1 in the Online Appendix) showed that although the pattern of our main findings was concentrated among boys-which is not a surprise considering how much higher conviction risks were among boys than among girls-girls also suffered the intergenerational transmission of crime.…”
Section: Step 2: Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Step 3: Heterogeneity and robustness checks Given the markedly higher crime rates among men compared to women, the intergenerational transmission of crime often is seen as primarily operating between fathers and sons (Andersen, 2018), and we therefore present our findings by child's gender. Results for boys and girls separately (see Figure A1 in the Online Appendix) showed that although the pattern of our main findings was concentrated among boys-which is not a surprise considering how much higher conviction risks were among boys than among girls-girls also suffered the intergenerational transmission of crime.…”
Section: Step 2: Main Resultsmentioning
confidence: 99%
“…These data consist of administrative records of a wide array of the lives of the population in Denmark, recorded by governmental as well as private agencies and reported to Statistics Denmark. All residents of Denmark have a unique personal identification number to which the administrative records are linked, allowing us to merge various types of information to individuals across different registries, such as demographic information from the population register, residence information from the housing register, and criminal records from the criminal justice registers (for additional details on Danish register data in relation to studies on the intergenerational transmission of crime, see Andersen, 2018).…”
Section: Data and Methods Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It takes two to tango, yet the literature has often ignored the female perspective on the intergenerational transmission of criminal justice contacts, likely due to men's overrepresentation in criminal statistics and studies of intergenerational transmission's reliance on last names to trace familial lines (however, see Andersen, 2018a;Burgess-Proctor, Huebner, & Durso, 2016;Hjalmarsson & Lindquist, 2013;Huebner & Gustafson, 2007;Muftić, Bouffard, & Armstrong, 2016 for contributions that consider maternal transmission). Further, focus has predominantly been on heterosexual couples and single parents, which at least to some extent likely is due to the nature of available data sources.…”
Section: The Role Of Maternal Criminal Justice Contactsmentioning
confidence: 99%
“…Last, as heavily documented in the literature, fatherhood does not happen in a vacuum, may be transformative, and may initiate desistance (Kerr, Capaldi, Owen, Wiesner, & Pears, 2011). Mother's criminal behavior also matters (Hjalmarsson & Lindquist, 2013), and there are strong evidence on assortative mating along lines of criminal involvement (e.g., Andersen, 2018a;Andersen, Andersen, & Skov, 2015). All these important processes have not been thoroughly considered in this study, but future work should seek to incorporate this perspectives to paint a more detailed picture of how differences not only in fertility, but also in the family situation, are important for fully understanding intergenerational transmission at a population level.…”
Section: Limitations Of Findingsmentioning
confidence: 99%